Effect of Temperature and Time Storage to pH and Color Changes of Palm Sap (Arenga pinnata Merr) after Tapping - Ansar Ansar ANSAR; Nazaruddin Nazaruddin; Atri Dewi Azis (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2019)
Flos masculus at palm can be produced a palm sap after tapping process. Palm sap have quality degradation due to effect environment temperature. The purpose of the study was to evaluate the effect of temperature and storage time to changes pH and color of palm sap after tapping. The research samples were obtained from farmers in Pusuk, West Lombok, NTB. The research parameters were observed is changes pH and color of palm sap during storage. The sample of the research was storaged at temperature variation of 10, 29, and 40oC, and then observed each 2 until 10 hour. The results of the research showed the temperature and time storage was affected to pH and color palm sap after tapping. After 10 hour pH of palm sap changed from 7.0 to 2.6 at temperature of 40oC, 4.8 at temperature of 29oC, and 6.6 at temperature of 10oC. Palm sap which storage at temperature 10oC has pH quality decrease is lowest than at temperature of 29 and 40oC. The higher temperature storage, the bigger pH decrease. The pH decreases, the L* and b* values also decrease significantly, but the value of a* does not change significantly at various storage temperatures.